Maqasid al-shari’ah: explorations and implications - El-Mesawi, Mohamed El-Tahir (Islamic Book Trust, 2018)
A ‘maqasid awakening’ (sahwah maqasidiyyah) has resulted in an increasingly large body of literature covering different aspects in the study of the goals and intents of Islamic law or maqasid al-shari’ah: conceptual, methodological, historical and practical. This surge involves not only students of Islamic jurisprudence and Shari’ah scholars, but also different categories of researchers and writers from the various disciplines of the humanities and social sciences to the natural and hard sciences. We could thus speak of the emergence of a new area of study bearing the name of ‘Maqasid studies’, in the same manner we talk of language studies, Qur’anic studies, hadith studies, etc. The present volume is an attempt to offer both a comprehensive and diversified view of maqasid al-shari’ah as a crucial and at the same time understudied subject in the English language, covering historical, theoretical and practical aspects thereof. The contributors’ sense of intellectual commitment, academic soundness and moral responsibility are certainly what accounts for its quality.